Pembuatan SELAT (Secang Latte) Bersama Ibu PKK sebagai Sarana untuk Meningkatkan UMKM di Kecamatan Rungkut - Nunik Hidayati; Febriarsita Eka Sasmita; Roidatus Shofiyah; Mirza Elmy Safira; Muhammad Yusron Maulana El-Yunusi; Didit Darmawan; Dharma Setiawan Negara (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
MSMEs contribute 61.07% of GDP, equivalent to 8.6 trillion. The Surabaya local government is developing MSMEs by encouraging its people through increasing creativity and innovation so that they can create new business ideas. The purpose of this service is to help produce an innovative drink that has many properties, explore the properties possessed by sappan wood and Indonesian spices in the drink, learn to design a creative and innovative business, help develop MSMEs in the region. The service method carried out is Asset Based Community Development (ABCD) because the area already has MSME assets in the form of wedang secang which needs product innovation to further expand the market. The results of this service increase sales of wedang secang MSMEs through new product innovations of secang with added milk.